Differences in Sexual Behavior and Partner Notification for Sexually Transmitted Infections Between the Out of School Youth and University Students in a Peri-Urban District in South Africa—A Cross-Sectional Survey - Mokgatle, Mathildah; Madiba, Sphiwe; Hlongwane, Naomi (Frontiers in Public Health, 2022)
The increase in sexually transmitted infections (STIs) in young people is a public health concern. Among those in university and out of school, different contextual factors contribute to their risky sexual behaviour and increased susceptibility to STIs and HIV. There are limited comparative studies examining risky sexual behaviour and partner notification (PN) between these two groups, particularly in South Africa. We investigated sexual behaviours, self-reported STI diagnosis, health seeking behaviour, and preferred PN methods of university students and out of school youth. A descriptive cross-sectional survey was used using convenient sampling to select 917 students across five health sciences universities and through periodic sampling 699 out of school youth were selected from two main local shopping centres in South Africa. Descriptive statistics, bivariate and multivariable logistic analysis were performed using Stata IC version 14. More university students (71.7%) than out of school youth were in casual relationships (28.3%), with half of out of school youth being in steady relations (50.2%). Moreover university students (65.7%) used a condom in the past six months compared to their counterparts (34.3%). Of the 124 youth who were diagnosed with STI in the past 12 months, majority (n = 106, 85% ) were out of school youth. The probability of notifying a partner about a STI infection was 82% among university students compared to their counterparts (p=>0.05). The odds of notifying a partner was 1.79 times more for those having multiple sexual partners than those who had only one partner. Both groups preferred a face-to-face STI disclosure with partner; however, more university students (67.%) preferred SMS notification than PN referral slips as compared to out of school youth (42%). Both the university students and the out of school youth engaged in risky sexual behaviours. Both groups preferred face-to-face and clinic SMS partner notifications, even though university students were in the majority. There is a need for developing health promotion scripts on disclosing STIs to sexual partners to empower the majority of the youth who prefer face-to-face PN over the prescribed methods.